Nutrition And Sanitation Interventions Through Community Engagement For Street Children: A Case Study Of Al-Ajyb - Yarliani, Ikta; Irayana, Ika; Pratiwi, Hardiyanti (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
This study is centered around enhancing nutrition and sanitation interventions by involving the community for the benefit of street children. The research takes place through community-based participatory research at the Al-Ajyb Child-Friendly School located in Pasar Sudimampir, Banjarmasin. The study investigates the interconnectedness of nutrition, sanitation, and health concerning street children and underscores the significance of early education and community engagement to address their distinct needs. Employing a blend of online and offline activities, the research brought together diverse stakeholders, including the Al-Ajyb Foundation, Banjarmasin Health Office, and the National Amil Zakat Agency of South Kalimantan Province, alongside educators and students from Al-Ajyb School. It delves into the challenges confronted by street children, encompassing issues of nutrition, hygiene, and constrained educational access. The research also spotlights the role of community-based interventions in fostering healthy behavior and enhancing awareness regarding the pivotal role of nutrition and sanitation. The study concludes with a pledge for collaborative endeavors among stakeholders to translate findings into tangible measures aimed at ameliorating the well-being and prospects of street children within the Sudimampir Market locality